Private-sector innovation processes in development cooperation: perspectives from Finnish technology enterprises - Hooli, Lauri J. (TAYLOR & FRANCIS LTD, 2022)
The development community has become an important financer of innovation processes in the Global South. This research scrutinizes Finnish private enterprises receiving development assistance for their innovation processes, targeting the markets of the Global South. Beyond the critical rationales, there is a lack of contextual understanding about the development impacts of private sector - focused development cooperation. The research reveals that the private sector's role in development is heterogeneous and complex. Although, companies' involvement has brought innovations, new actors, and funding to development cooperation, it has only fragile ties to the conventional objectives of development - to reduce extreme poverty and inequality. Innovation activities of the Finnish companies focus on rather developed markets of middle-income countries and an educated wealthy minority. Local communities have minor involvement in the design, profit sharing, or value addition of such projects, and their main role is the consumption of end products.